Virtual Learning Space for Kindergarten - Yusoff, Nurul Liza (Universiti Teknologi Petronas, 2008)
This report covers the final draft of the study in which the title Virtual Learning Space for Kindergarten has been researched. The Virtual Learning Space for Kindergarten is developed using Macromedia Dreamweaver, Macromedia Flash MX 2004, Barbarosa Gif Animator and Adobe Photoshop 7.0. This project is carried out using Waterfall System Development Life Cycle Model. The Virtual Learning Space for Kindergarten will assist the kindergarten kids since "Children are active thinkers who are constantly trying to construct new strategies and advanced understandings" (Piaget). As the word kids might propose several definitions and explanation to different individual, this research stress on kindergarten kids whose ages are between 4 to 6 years old. Several meaningful findings are made during the research, which suggestively enable the author to tackle the matter in a broader view. By using the integration of multimedia which is the combination of sounds, animations and text, Virtual Learning Space for Kindergarten helps kindergarten kids in Malaysia, to enhance their learning. The emphasis will shift from chalk-and-board method to interactive digital content delivered via the Internet. With sufficient access and support, teachers will be better able to help their students to understand concepts and engage in learning and to provide them with access to information and resources and better meet the students' individual needs. Technology opportunities presented leads to the enhancement of learning and improve students' achievement. It can enrich the exchange between kids and their families at home as schools are looking for greater parental participation in their children's educational. Virtual Learning Space for Kindergarten gives even the busiest parents an affordable and easy means to participate in their child's lessons and even work cooperatively with teachers where they can explore the world together. In the best of all worlds, parents and educators would be 'attached at the hip', working side by side, sharing information and planning opportunities to enrich kids' learning experiences at home and in the classroom.